2015
DOI: 10.3390/ijerph120911050
|View full text |Cite
|
Sign up to set email alerts
|

The Use, Perceived Effectiveness and Safety of Herbal Galactagogues During Breastfeeding: A Qualitative Study

Abstract: The World Health Organization recommends breastfeeding as the normal infant feeding method and that infants being breastfed should be regarded as the control group or norm reference in all instances. There are many factors which could contribute to a new mother ceasing breastfeeding early, with the most commonly reported reason being perceived insufficient breast milk supply. The use of herbal galactagogues is increasingly common worldwide. Literature review identified a need for more research in the area of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 48 publications
4
60
0
5
Order By: Relevance
“…There are different dosages and forms of galactagogue preparation available23 and another recent study has illustrated that the methods of administration among users vary significantly 22. This is also reflected by the absence of evidence-based clinical guidelines to assist providers in choice and appropriate dosage of galactagogues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different dosages and forms of galactagogue preparation available23 and another recent study has illustrated that the methods of administration among users vary significantly 22. This is also reflected by the absence of evidence-based clinical guidelines to assist providers in choice and appropriate dosage of galactagogues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among lactating women using galactagogues revealed that most women using these substances perceived them to be effective, with fenugreek and blessed thistle being used most frequently, and often in combination 2225. Furthermore, women also expressed the notion that herbal galactagogues are safer compared to conventional medicine and expected providers to be aware of the different options and hence able to provide adequate advice 26.…”
Section: Introductionmentioning
confidence: 99%
“…The galactagogue plants can provide valuable support, although it is crucial to know that some of their active constituents may cause side effects in both mothers and their infants. This fact argues for increased public awareness and for available information on the safety implications of using herbal medicines to be provided at least among breastfeeding women [38]. The species cited in this study are mainly vegetables commonly utilized by local populations with high nutritional profiles, which can improve the quality and quantity of milk produced by mothers.…”
Section: Discussionmentioning
confidence: 97%
“…с соавт. (2015) подчеркивает-ся важность потенциальных психологических преиму-ществ использования травяных лактогонных средств [22]. Восприятие лактации как недостаточной распро-странено среди кормящих женщин и в послеродовой период, и в дальнейшем, что приводит к тревоге, кото-рая, в свою очередь, может ухудшить ГВ и самочувствие женщины [60].…”
Section: в исследованияхunclassified
“…В рекомендациях Амери-канской академии грудного вскармливания и ВОЗ особое внимание уделено оптимизации методов кормления [20,3]. Показаниями для назначения лактогонных средств являются недостаточная продукция молока, сохраняюща-яся после применения нефармакологических методов у здоровых матерей, а также возникшая вследствие дли-тельного разлучения матери и ребенка (например, в палатах интенсивной терапии), или необходимость ини-циации лактации [21,22].…”
unclassified